PENDEKATAN FENOMENOLOGI DALAM STUDI ISLAM - Mujib, Abdul (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2015)
Phenomenological approach has its own characteristics that are different from other approaches to understanding agama.Pendekatan phenomenology is a method to what is experienced by religion, what is felt, said and done, and how well the experience meaningful for him. There are two approaches religious phenomenology, First, phenomenology is a method for understanding the religion of someone who include most businesses in assessing options and their commitment neutrally as preparation for the reconstruction of the experiences of others. Second, the construction of the taxonomic scheme for classifying phenomena blasted with cultural boundaries and religious groups. In general, the approach fenomologi just caught the side of religious experience and religious reaction similarity of all human beings equally, regardless of the dimensions of space and time and cultural differences. Truth phenomenological study is an explanation of the meaning of rites, rituals, ceremonies, doctrine, or social relations and in religious actors. Religion as a chain of authoritative tradition implies that religions should be understood as a religion, not because they believe or do not believe in God, spirit or partially transcendent form, but because of their beliefs transmits and strengthens the authority of tradition.